Unconventional Fossil-Based Fuels Economic and Environmental Trade-Offs - Toman, Michael (RAND Corporation, 2008)
In this report, RAND researchers assess the potential future production levels, production costs, greenhouse gases, and other environmental implications of synthetic crude oil from oil sands and fuels produced via coal liquefaction relative to conventional petroleum-based transportation fuels. The findings indicate the potential cost-competitiveness of these alternative fuels and potential economic-environmental trade-offs from their deployment.